Tracer Study of Bachelor of Science in Tourism Management Graduates from Camarines Sur Polytechnic Colleges: 2018 and 2019 Cohorts - Sotero, Maria Luisa O.; Brioso, Jessa C.; Baraquil-Frongoso, Mary Jane S.; Orosco-Nunez, Sharmine (The Indonesian Institute of Science and Technology Research, 2024)
This research is primarily a tracer study on alumnae of the Bachelor of Science in Tourism Management (BSTM) program at the Camarines Sur Polytechnic Colleges in Nabua, Camarines Sur, from 2018 to 2019. It tried to ascertain the individual's personal, professional, and employment profile. Additionally, it found factors for employees' retention in their present or former positions and their happiness with their current or previous jobs. Similarly, the study examines respondents' perceptions of the program's perceived benefits to themselves. Respondents were asked to rate the program personally for each indicator. More so, this research makes recommendations for enhancing the employability of BSTM alumnae. This study employed a descriptive survey method. Respondents included BSTM alumnae. Most graduates find meaningful employment in private enterprises, primarily in hospitality-related roles. Their employability was influenced by socioeconomic, academic, and school characteristics. The environment significantly affects an employee's ability to retain their employment. There is still significant room for improvement in the college's BSTM program, particularly topic offerings and extracurricular activities.